2014
DOI: 10.1111/wvn.12060
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the Effectiveness of Mentoring as a Knowledge Translation Intervention for Implementing Empirical Evidence: A Systematic Review

Abstract: BackgroundMentoring as a knowledge translation (KT) intervention uses social influence among healthcare professionals to increase use of evidence in clinical practice.AimTo determine the effectiveness of mentoring as a KT intervention designed to increase healthcare professionals’ use of evidence in clinical practice.MethodsA systematic review was conducted using electronic databases (i.e., MEDLINE, CINAHL), grey literature, and hand searching. Eligible studies evaluated mentoring of healthcare professionals r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
65
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 69 publications
(77 citation statements)
references
References 49 publications
(130 reference statements)
6
65
0
1
Order By: Relevance
“…Nursing: One study included in Abdullah et al found telephone mentoring improved "all measured outcomes" but did not specify further [28].…”
Section: E-mentoring and Distance Mentoringmentioning
confidence: 99%
See 4 more Smart Citations
“…Nursing: One study included in Abdullah et al found telephone mentoring improved "all measured outcomes" but did not specify further [28].…”
Section: E-mentoring and Distance Mentoringmentioning
confidence: 99%
“…In nursing 2 postgraduate [25,38] Abdullah et al review of mentoring in medicine and nursing found dyadic mentoring enhanced learning [28].…”
Section: Dyadic Mentoring Modelmentioning
confidence: 99%
See 3 more Smart Citations